Select all expressions that are equivalent to 6x + 1 - (3x - 1)
1 answer:
Answer:
=3x+2
Step-by-step explanation:
Let's simplify step-by-step.
6x+1−(3x−1)
Distribute the Negative Sign:
=6x+1+−1(3x−1)
=6x+1+−1(3x)+(−1)(−1)
=6x+1+−3x+1
Combine Like Terms:
=6x+1+−3x+1
=(6x+−3x)+(1+1)
=3x+2
Let's simplify step-by-step.
6x+1−(3x−1)
Distribute the Negative Sign:
=6x+1+−1(3x−1)
=6x+1+−1(3x)+(−1)(−1)
=6x+1+−3x+1
Combine Like Terms:
=6x+1+−3x+1
=(6x+−3x)+(1+1)
You might be interested in
The first equation has a solution of X=-5
1. 371.25
2. 742.5
3.185.625
2 hours.
hope this helped
Answer:
He began with 14 please mark brainliest
Step-by-step explanation:
13-6 equals 7
7 times 2 equals 14
The new mean age will be greater than 14.2 years because the teacher is older than the previous mean.